An Analysis of Freedom to Learn Currciulum Understanding and Readiness on Primary School Education Department FIP UMJ - Dendi Wijaya Saputra; Muhamad Sofian Hadi (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This Study aims to describe and analyze students’ understanding of the freedom to learn curriculum (Kurikulum Merdeka), spesifically among undergraduate and Postgraduate students of the Primary School Education Department at the Faculty of Educational Sciences, Muhammadiyah University of Jakarta. The researchers use phenomological approach as a type of the qualitative study to closely and comprehensively explane individual understandings based on personal experience. Setting of the study took place at primary school education department faculty of education Muhammadiyah University of Jakarta. Data collection techniques used in this study consist of observation, interview and documentation. The results of the study indicate that postgraduate students demonstrated a high level of understanding of the Freedom to Learn Curriculum, while undergraduate students showed a relatively lower level of comprehension. As the conclusion of the study, it can be conclude that postgraduate students have a better understanding of the Freedom to Learn Curriculum compared to undergraduate students.